Fuori Uso '98 - Fuoriuso 1998 - Benedetti, Lorenzo; Corbetta, Caroline; Mancini, Alessandra; Pietrantonio, Giacinto Di; Rabottini, Alessandro; Santomo, Valentina (Pescara : Associazione Culturale Arte Nova, 1998)
Airo, Mario ; Araki, Nobuyoshi ; Bartolini, Massimo ; Berti, Simone ; Brener, Alexander ; Chia, Sandro ; Cucchi, Enzo ; Dion, Mark ; Doherty, Willie ; Garutti, Alberto ; Gabellone, Giuseppe ; Gillick, Liam ; Goldin, Nan ; Höller, Carsten ; Kcho ; Kaprow, Allan ; Maloney, Martin ; Manetas, Miltos ; Manzelli, Margherita ; Morris, Sarah ; Mullican, Matt ; Neshat, Shirin ; Oppenheim, Dennis ; Piper, Adrian ; Prini, Emilio ; Rehberger, Tobias ; Sarra, Sergio ; Serrano, Andres ; Spalletti, Ettore ; Tiravanija, Rirkrit ; Veilhan, Xavier ; Vitone, Luca ; Wearing, Gillian
Fuori Uso '98 - Fuoriuso 1998, Pescara, 20-21-22 giugno - 2 agosto 1998
Italiaans & Engels
boek